Outcomes of robotic-assisted surgery for pediatric renal tumors: a systematic review - Amani N. Alansari (19743643) (2025)
Robotic-assisted surgery (RAS) has gained interest due to its precision and minimally invasive advantages. However, its adoption in pediatric renal tumors remains limited, with concerns about feasibility, safety, and oncological outcomes. This systematic review summarized the literature evaluating the outcomes of RAS for pediatric renal tumors. We searched PubMed, Scopus, and Web of Science for studies on RAS in pediatric renal tumors. We considered all primary studies including case reports, case series, and cohort studies. Quality was assessed using Joanna Briggs Institute (JBI) critical appraisal tools. A total of 14 studies, including 7 case reports, 5 case series, and 2 cohort studies, with 79 pediatric patients undergoing RAS for renal tumors were included. Conversion to open surgery occurred in 6.3% of cases. Renal vein injury was reported in 2.5%. Operative times ranged from 90 to 360 min, with shorter durations for partial nephrectomies. Blood loss was highly variable, from < 5 mL in smaller tumors to > 350 mL in complex cases. Hospital stays ranged from 2 to 7 days, with one outlier requiring a 4-week hospitalization. Oncological outcomes were generally favorable, with 96.2% of patients remaining disease free at follow-up. However, three patients (3.8%) experienced local recurrence, and two patients (2.5%) with WT died due to CNS metastases. This systematic review demonstrates that RAS is a feasible and safe approach for managing pediatric renal tumors. However, larger studies with extended follow-up are necessary to validate long-term oncological outcomes and refine patient selection criteria. Other Information Published in: Journal of Robotic Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11701-025-02473-4